RISK PROFILE, GCG, EARNINGS, CAPITAL, PROFITABILITY, THE HEALTH of BUMN BANKS LISTED on THE IDX - l Aulia, Diniatul; Inayah, Nur Lailiyatul; Apriliasari, Ria Dini; Kusuma Devi, Fitriyah; Habibie Al Hamzah, Muhammad (Yayasan Nuraini Ibrahim Mandiri, 2024)
This study aims to determine the effect of research variables on profitability. The ratios used in this study are Risk Profile, Good Corporate Governance, Earnings and Capital as independent variables while the dependent variable in this study is Profitability. The population of this study is state-owned banks listed on the Indonesia Stock Exchange in 2015-2022. The sample selection was carried out by purposive sampling method and from 47 banks listed on the IDX obtained 4 samples of BUMN banks. The data used is secondary data. The analysis technique used is the classic assumption test, multiple regression analysis and hypothesis testing. Based on the results of the analysis it can be concluded that the Risk Profile, Good Corporate Governance, Earnings and Capital variables simultaneously affect Profitability, In this study it can be seen that the Earnings variable is the most dominant variable on Profitability.